Abstracts Accepted for Publication 2019
DOI: 10.1136/annrheumdis-2019-eular.4127
|View full text |Cite
|
Sign up to set email alerts
|

Ab0082 reduced Steroidogenic Activity of Repository Corticotropin Injection (Rci) Induces a Distinct Cytokine Response Following T Cell Activation in Vivo

Abstract: Background:Melanocortin receptor agonists, such as αMSH have been shown to reduce inflammation in preclinical models, suppressing the production of proinflammatory cytokines. Natural and synthetic ACTH analogues remain linked to the induction of corticosteroids as their primary mechanism of action, leading to the anti-inflammatory and immunosuppressive responses. Repository Corticotropin Injection (RCI) is a complex mixture containing purified porcine pituitary ACTH-analogue, and is an FDA-approved treatment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…Treatment with Acthar Gel has also been effective in patients with rheumatoid arthritis or glomerular diseases that have been resistant to corticosteroid treatment, further confirming a mechanism of action that is independent of cortisol production [48,49]. Thus, these data, in combination with preclinical and clinical studies [24][25][26]28,48,49], suggest that Acthar Gel may provide benefit in the treatment of inflammatory disease through mechanisms beyond the induction of steroids.…”
Section: Mcr Agonist Mcr Rank Order Acthar Gelmentioning
confidence: 67%
See 3 more Smart Citations
“…Treatment with Acthar Gel has also been effective in patients with rheumatoid arthritis or glomerular diseases that have been resistant to corticosteroid treatment, further confirming a mechanism of action that is independent of cortisol production [48,49]. Thus, these data, in combination with preclinical and clinical studies [24][25][26]28,48,49], suggest that Acthar Gel may provide benefit in the treatment of inflammatory disease through mechanisms beyond the induction of steroids.…”
Section: Mcr Agonist Mcr Rank Order Acthar Gelmentioning
confidence: 67%
“…Taken together, the combined engagement profile of Acthar Gel at MC1R, MC3R, MC4R, and MC5R suggests a distinct direct immune cell effect beyond the indirect antiinflammatory effect from MC2R-dependent production of corticosteroids. Despite less sustained cortisol induction, Acthar Gel remains efficacious [48,49], suggesting direct interaction with immune cells to treat disease [24][25][26]. The mechanism of action of Acthar Gel is unique from that of pACTH 1-39 , ACTH 1-24 , N25D-ACTH 1-39 , and other MCR agonists, suggesting that its complex mixture of peptides interacts with MCRs differently than any single MCR agonist does.…”
Section: Mcr Agonist Mcr Rank Order Acthar Gelmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of clinical characteristics, treatment patterns, and HCRU before initiation of RCI, versus initiation or continuation of ts/ bDMARD therapy, is critical in understanding differences in patients with uncontrolled RA requiring alternatives to standard therapy and in generating an accurate patient profile for RCI initiators. Repository corticotropin injection is a complex mixture of adrenocorticotropic hormone analogs and other pituitary peptides that activates all five melanocortin receptors (MC1R-MC5R), inducing steroidogenesis, antiinflammatory effects, and direct immunomodulation of B and T cells [28][29][30][31][32]. Recently, Montero-Melendez et al demonstrated activation of MC1R-induced cellular senescence in both synovial and dermal fibroblasts in a mouse model of inflammatory arthritis [33].…”
Section: Discussionmentioning
confidence: 99%